Pengaruh Pembelajaran Online terhadap Stres Akademik Siswa Di SMA Negeri 1 Kepanjen - Syarifatur Rofiah (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2021)
Changes in learning patterns occurred in Indonesia during the Covid-19 pandemic outbreak. Face-to-face learning patterns, which are usually carried out at all levels of high school education and above, must be replaced by online or online learning. This is done to prevent the spread of covid-19. This study aims to determine the effect of online learning on student academic stress during the Covid-19 pandemic. The research used was analytic observational with cross sectional approach. The research was conducted in November 2020 with 285 respondents from SMA Negeri 1 Kepanjen. The results of the study indicate that there is an effect of online learning on academic stress experienced by students in school. Online learning requires support from various parties, both government and schools. Keywords:Online Learning; Academic Stress; Students